(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Emotional intelligence (EI) has been hailed as one of the factors influencing job performance, job satisfaction, and burnout. There are three theories; they are the ability model which views EI as a mental capability, the traits model which views EI as a personality trait and a mixed-model approach which evaluates an individual based on personal perceptions. Organisational culture has been shown to be associated with corporate emotional intelligence. The aim of this article is to carry out systematic literature review on emotional intelligence and its association with organisational culture. In this systematic literature review, 93 records from 2005-2022 were identified through Web of Science (WoS) and Scopus on emotional intelligence and organisational culture. A total of 21 records out of 93 records were removed based on the exclusion criteria. Six records were removed due to duplication. Out of the remaining 66 records, 57 were deemed not fitting the research question, with two full text articles unavailable. A total of nine records finally were deemed suitable for analyses. There are six articles on leadership, two articles on knowledge, and one article on decision making. All the articles were analysed and 3 themes have emerged on the topic of organisational culture and emotional intelligence, which are leadership, knowledge dissemination, and decision making. The systematic literature review has shown the link between emotional intelligence and organisational culture. Leadership, knowledge dissemination, and corporate decision-making are dimensions which are associated with organisational culture and it gives impact to the organisational emotional intelligence.